Ethical decision making of earnings management: applying the theory of planned behaviour - Demikha, Lotfi (Kulliyyah of Economics and Management Sciences, International Islamic University Malaysia, 2012)
Managers repeatedly tend to select accounting choices that affect earnings either positively or negatively. According to GAAP, the usage of accounting choices is not an explicit indication of managing earnings due to the inconclusive discussion about the morality of such action among users and regulatory authorities. To highlight this issue from an Islamic perspective, this study is motivated by the significant losses suffered by investors in companies electing to engage in questionable accounting practice. It is further motivated by the will to understand the attitude of managers from a religious perspective. The objective of the study is to ground the ethical issue of Earnings Management (EM) and to explore the impact of religious family background, religious practices and ethics education in orienting the decision making of managers toward the practice of EM. More specifically, this study aims to test whether the Islamic ethics plays an influential factor on the behaviour of Muslims' managers. This study also seeks a better understanding the construct of behavioural intention of managers. To do so, the study was implemented in three universities IIUM, UM and UPM. Using a sample of 104 MBA, Master accounting and finance students from three universities, the current study proposed a casual model to explain an individual's judgment with respect to an ethical question for managers. This study established its analysis on the framework of the theory of planned behavior. This study has come up with two primary results (1) religion has a minor impact on the managers' attitude in terms of the practice of EM. (2) Religion in general including Islamic religion does not lower the practice of EM in this particular study. These unexpected results can be pertained to the strong influence factor of western thinking in separating religion from life.